Strategi Dakwah Ustad Anwar Pohan Dalam Meningkatkan Pemahaman Agama Islam Di Dusun Pengkolan Desa Luat Lombang Kecamatan Sipirok - Simanjuntak, Imelda; Kustiawan, Winda (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
This study aims to analyze the da'wah strategy used by Ustad Anwar Pohan in increasing the understanding of Islam in Pengkolan Hamlet, Sipirok District. The research method used is a qualitative method with a descriptive approach. Data collection techniques researchers use observation, interviews and documentation. Data analysis with Miles and huberman and data validity using triangulation of sources and time. The results showed that Ustad Anwar Pohan used various da'wah strategies which included educational approaches, personal interactions, local context adaptation, responsiveness to input, use of local languages, da'wah through Friday sermons, and consistency in da'wah. The community's perception shows that the da'wah activities carried out by Ustad Anwar Pohan are positive and have the support of the local community regarding the delivery of da'wah which is able to provide an understanding of Islam to them. As for them, it is only due to differences, religious views, differences, approaches used, and personalities where the delivery is harsh and loud. The supporting factors for the da'wah carried out by Ustad Anwar Pohan are the people who attend da'wah studies from day to day have increased, although a little but still experiencing an increase. One of the inhibiting factors is the existence of religious understanding and practices that are deeply embedded in some communities. Some people may have practiced different religious traditions for a long time, and it is difficult for them to accept a new understanding of Islam.